Cultivation Experiment of Cowpea Covered with Insect-proof Net - Xuejie, Feng; Yueyan, Wu; Changzhi, Deng; Xueqiao, Li (Plant Diseases and Pests(植物病虫害研究：英文版), 2014)
The most serious potential hazard of cowpea product is the pesticide residue for controlling such pests as thrips and cowpea pod borer. To explore a safe and efficient mode of cowpea production that is fit for climatic characteristics of Hainan, ensure the safety of cowpea supply, minimize the use of pesticides, and control pests in physical means, insect-proof nets are applied in cowpea cultivation. We set 5-mm, 2.5-mm and 1.67-ram insect-proof nets as three treatments and open filed cultivation as CK to explore efficiency of insect-preof net in cowpoa production in terms of insect-proof efficiency, biological characters and commodity properties and yield of cowpea. The results showed that insect-proof cultivation was efficient in controlling pests, especially the 2.5-mm net showed the optimal effect for cowpea production.